P42 The UCEIS score can help predict the long-term outcome of UC patients in clinical remission. (19th June 2022) - Markopoulos, Panagiotis; Ghuman, Sundeep; Zeki, Sebastian; Dart, Robin; Ray, Shuvra; Anderson, Simon; Mawdsley, Joel; Irving, Peter; Samaan, Mark
Abstract : Introduction: The UCEIS is a validated index that can be used to accurately measure endoscopic disease activity in Ulcerative Colitis. The IOIBD STRIDE initiative recommended a composite UC treatment target consisting of both clinical and endoscopic remission. However, there exists no widely accepted definition for endoscopic remission using UCEIS. Although previous data has suggested that UCEIS values > 3 generally prompt treatment escalation, we aimed to investigate what threshold could be used to predict long-term favourable outcomes of UC patients in clinical remission. Methods: A total of 358 UC patients in clinical remission at the time of endoscopic assessment (sigmoidoscopy or colonoscopy) between March 2016 and October 2020 were included in our retrospective cohort study. Clinical disease activity was assessed within 2 months before the endoscopy; remission was defined by a Simple Clinical Colitis Activity Index (SCCAI) < 4. Biochemical markers and UCEIS values were reviewed at the time of endoscopy and disease course was followed up to November 2021. The mean duration of follow-up was 2.2 years (range 1-5 years). ROC, Kaplan-Meier curves, logistic regression and chi square tests were used in the data analysis. Reults: A strong correlation was observed between the UCEIS values and subsequent clinical course. UCEIS value of 3 represents the cut-off point, above which UCEIS values are significantly correlated with increased risk of recurrence (sensitivity=0.6, 1-specificity=0.2, area under curve 0.737). UCEIS < 3 was correlated with significantly higher rates of long-term remission ( Figure 1 ). A multivariate analysis indicated that a bleeding sub-score of 0 and an erosion/ulceration sub-score of 0 are both significantly correlated with subsequent sustained clinical remission (both p≤0.01). In the patients with a UCEIS 3 (cut-off), none of the sub scores were significantly superior to the others in predicting clinical outcome. In addition, a significant correlation between UCEIS values and CRP was confirmed. For a UCEIS <3, the CRP was usually normal, whereas a UCEIS >4 was associated with a raised CRP (area under curve 0.721, p 0.00). Conclusion: Our study demonstrates the value of endoscopic assessment using UCEIS for the prediction of long-term outcomes of UC patients in clinical remission. A UCEIS score of 3 appeared to be a threshold, above which rates of recurrence increase significantly. The absence of bleeding or mucosal erosions/ulceration also indicates the likelihood of sustained clinical remission. A UCEIS score of 3, particularly in the presence of mucosal damage (bleeding or ulcerations), could suggest the need for treatment escalation even in the context of clinical remission.